SMALLHOLDERS’ PRIORITIES IN FINANCING: MATHEMATICAL APPLICATIONS IN THE CONTEXT OF A POST-TRANSITION ECONOMY - Ivana JANESKA STAMENKOVSKA; Ana SIMONOVSKA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Smallholders in the North Macedonia face different constraints in accessing to finance. Various formal institutions, mechanisms and support programmes were established to increase the external capital consumption by farmers, but still smallholders remained underserved with appropriate finance. The aim of this study is to determine the priorities of the smallholders in choosing their best alternative of financial sources under different financing incentives. The Analytical Hierarchy Process, as a multi-criteria decision making technique, enabled prioritisation in the complex financial decision- making, considering multiple conflicting criteria at once. The results show that the smallholders mostly need finance to support investments in farm modernization, followed by the need of investment capital for adaption and mitigation of negative climate change effects and environment protection. In order to meet these needs, smallholders mostly prioritise the national institutions for providing financial support in agriculture. Especially important for the smallholders is the National Rural Development Programme and IPARD Programme that follow complex procedures, and thus, these funds have a relatively low utilisation rate. Another priority of smallholders is given to the direct credits by the National Development Bank that are currently unavailable to smallholders due to legal restrictions. Analyses of this kind, considering the bottom-up approach in valuing the smallholders’ opinions and needs of financing, are scarce in the practise, but they are very important in tailoring the financing offer and financial support measures in agriculture to the real needs of the smallholders.